Strengthening The Presidential System Through Mechanisms of Public Oversight of The President - Rachman, Adinda; Nadir Nadir; Puspitasari, Yuni; Arisandi, Erfan (International Journal of Law and Society, 2025)
This research aims to analyze Indonesia's presidential system of government through mechanisms of popular control over the president. In a presidential system of government, the president holds full executive power, separate from the legislative and judicial branches. This power must be balanced with strong control mechanisms to prevent abuse of power. One important form of oversight that often receives insufficient attention is direct popular control over the president. The method employed in this research is a juridical-normative method with statutory and conceptual approaches, supported by primary and secondary legal sources, with legal materials collected through literature study. The findings of this research indicate that mechanisms of popular control over the president remain weak, both through legal and political instruments. The impeachment mechanism stipulated in Article 7A of the 1945 Constitution of the Republic of Indonesia is extremely complex. Meanwhile, the oversight function of the House of Representatives (DPR) as the people's representative also does not operate optimally due to the dominance of oversized coalitions, which cause parliament to tend to favor the government. Strengthening popular control functions is not intended to weaken presidential power, but rather to ensure that executive power operates in an accountable and transparent manner while remaining subject to the principle of popular sovereignty, so that Indonesia's presidential system becomes more democratic and enjoys strong legitimacy in the eyes of the people.